Marketing Strategy Analysis at Yamaha Matramas Motor Dealers in Makassar - Furkan (Journal AGENCY, 2022)
The purpose of this research is to find out the strengths, weaknesses, opportunities and threats of the company and also to find out alternative strategies that can be used by the company, in this case Yamaha Matramas Motor Dealers. The data analysis technique used is SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The meaning of this analysis is to identify the company's internal and external environment in a competitive climate with companies engaged in the same business field. SWOT analysis includes the external environment and the internal environment. Environmental analysis is a process used to determine strengths, weaknesses, opportunities and threats. In this SWOT analysis, a qualitative approach will be used. The qualitative approach is an analysis that is used without using numerical calculations, but is based on judgments or opinions as well as basics that can support subjective decision making. Based on all the analyzes mentioned above, the tool used to compile the company's strategic factors is to use the SWOT matrix. This matrix can clearly describe how the external opportunities and threats faced by the company can be adjusted to the internal strengths and weaknesses of the company. The matrix can generate four sets of possible alternative strategies. By using a SWOT analysis, it can be concluded that the company can take an alternative strategy of ST, WT, SO and WO.